Single‐Electron Pumps and Quantum Current Metrology in the Revised SI. Issue 5 (30th January 2019) - Scherer, Hansjörg; Schumacher, Hans Werner
Abstract: The consequences of the revision of the International System of Units for electrical quantum metrology are discussed herein. Possible applications of single‐electron transport pump devices and other topical state‐of‐the‐art metrology methodologies based on quantum electrical effects are reviewed, with a focus on their potential for and implications on electrical metrology in the future. Abstract : The consequences of the revision of the International System of Units for electrical metrology are reviewed. The electrical base unit Ampere is focussed upon, along with the possible primary realization of the unit based on electrical quantum metrology. The generation of quantized currents by single electron pumps and their impact on electrical metrology is discussed. Additionally, other state‐of‐the‐art metrology methodologies based on quantum electrical effects are reviewed, with focus on their potential for future electrical metrology.